In vivo, high-resolution, three-dimensional imaging of port wine stain microvasculature in human skin - Liu, Gangjun; Jia, Wangcun; Nelson, J. Stuart; Chen, Zhongping (Lasers in surgery and medicine, 2013)
Background and Objectives Port‐wine stain (PWS) is a congenital, progressive vascular malformation of the dermis. The use of optical coherence tomography (OCT) for the characterization of blood vessels in PWS skin has been demonstrated by several groups. In the past few years, advances in OCT technology have greatly increased imaging speed. Sophisticated numerical algorithms have improved the sensitivity of Doppler OCT dramatically. These improvements have enabled the noninvasive, high‐resolution, three‐dimensional functional imaging of PWS skin. Here, we demonstrate high‐resolution, three‐dimensional, microvasculature imaging of PWS and normal skin using Doppler OCT technique. Study Design/Materials and Methods The OCT system uses a swept source laser which has a central wavelength of 1,310 nm, an A‐line rate of 50 kHz and a total average power of 16 mW. The system uses a handheld imaging probe and has an axial resolution of 9.3 µm in air and a lateral resolution of approximately 15 µm. Images were acquired from PWS subjects at the Beckman Laser Institute and Medical Clinic. Microvasculature of the PWS skin and normal skin were obtained from the PWS subject. Results High‐resolution, three‐dimensional microvasculature of PWS and normal skin were obtained. Many enlarged PWS vessels are detected in the dermis down to 1.0 mm below the PWS skin surface. In one subject, the blood vessel diameters range from 40 to 90 µm at the epidermal–dermal junction and increase up to 300–500 µm at deeper regions 700–1,000 µm below skin surface. The blood vessels close to the epidermal–dermal junction are more uniform, in terms of diameter. The more tortuous and dilated PWS blood vessels are located at deeper regions 600–1,000 µm below the skin surface. In another subject example, the PWS skin blood vessels are dilated at very superficial layers at a depth less than 500 µm below the skin surface. The PWS skin vessel diameters range from 60 to 650 µm, with most vessels having a diameter of around 200 µm. Conclusions OCT can be used to quantitatively image in vivo skin micro‐vasculature. Analysis of the PWS and normal skin blood vessels were performed and the results can provide quantitative information to optimize laser treatment on an individual patient basis. Lasers Surg. Med. 45:628–632, 2013. © 2013 Wiley Periodicals, Inc.